The Influence of Principal Leadership and Teacher Professionalism on Learning Effectiveness at State Junior High School of Selat District Kapuas Regency - Harini Irawati; Akhmad Abdurahman; Riky Welli Saputra (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify and analyze the influence of the principal's leadership on the effectiveness of learning at Selat State Middle School, Kapuas Regency. and Knowing and analyzing the effect of teacher professionalism on the effectiveness of learning at Selat State Middle School, Kapuas Regency. The study population was all teachers at State Junior High Schools in Selat District, Kapuas Regency, and the sample was drawn using the Probability Sampling technique with as many as 44 people using the Slovin formula.